If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 2 + x = 6 Combine like terms: 2 + 2 = 4 4 + x = 6 Solving 4 + x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + x = 6 + -4 x = 6 + -4 Combine like terms: 6 + -4 = 2 x = 2 Simplifying x = 2
| 2r-3=18 | | 11+2g=2g-(g-15) | | 3x+5=5y-8 | | w-1=5w+3w-8 | | 7p+11=3p | | 3+d=9-d | | 2(x+4)+(5x)=7(x+4)-5 | | 4c-3=17 | | 15-3.7m=12.84-2.5m | | -9(3y-4)=-531 | | 5(a-1)=2a+4(a-1) | | 5x+8(x+1)+3=11-3x | | 2(7h-3)=120 | | 4-4(x-3)=20 | | 8-5=11 | | -(1-x)=2(3x-1) | | 9y-6+y=-(y+5y) | | 7r+11r=725-7r | | 5(b+1)=5b+1 | | -25=7+4x | | 5(2x-31)+3=10x-155 | | 6(x-8)-3x=5(x-1)-1 | | 3+5-6+2x=-4(x-3)+7 | | -9(4x-2)=108-6x | | 4(2x+2)=7x+1 | | 6x+3x-x=96 | | 2c-11c+5=0 | | 2(m-3)=2(m-6) | | 5x^2-30x+100=0 | | 4(-5-x)=10-2x | | -.25x-9=.90 | | 8-h=-4 |